Halogen‐content‐dependent photoluminescence of Mn2+‐doped CsPbCl3 nanocrystals. Issue 7 (27th March 2022) - Wang, Nanchuan; Guo, Shibo; Chen, Qiaochu; Gao, Fengmei; Yang, Weiyou; Fu, Hui; Zheng, Jinju
Abstract: The thermodynamically viable halogen vacancy defects in CsPbCl3 perovskite nanocrystals (NCs) are considered the main factor in weakening their optical quality. However, their separate impact on the dopant emission in Mn 2+ ‐doped CsPbCl3 perovskite NCs is still under exploration owing to the absence of comparable samples. Herein, a series of Mn 2+ ‐doped CsPbCl3 samples were synthesized with different oleylamine‐Cl (OAm‐Cl) contents based on a halogen‐hot‐injection strategy. It is found that the Mn 2+ concentration of as‐prepared samples fixed at 0.65%, and the Mn 2+ photoluminescence (PL) also exhibited an OAm‐Cl content‐independent lifetime of ∼ 1.78 ms, implying the efficient and identical luminescence of isolated Mn 2+ ion in all samples. In contrast, the excitonic and Mn 2+ PL intensities of the NCs are strong related to the amount of OAm‐Cl, which are attributed to the coordination effect of the suppressed excitonic nonradiative recombination owing to the passivation of chloride vacancies and the enhanced energy transfer from the host exciton to Mn 2+ ions in the samples with sufficient OAm‐Cl contents. The temperature‐dependent of Mn 2+ PL disclosed an initial increase and was followed by a decrease with increasing temperature for the samples with relatively higher OAm‐Cl contents, while it monotonously decreases for the sample with lower OAm‐Cl content of 0.4 mL. The different PL intensity change trend results from the effective passivation of chloride vacancies by extra OAm‐Cl. Above results present here will help clarify the underlying influence mechanism of halogen vacancy on the PL properties of Mn 2+ ‐doped perovskite NCs, which is essential for targeted modulation of their optical properties.